In the recursive series:

  • $a_{0}=60$
  • $a_{n+1}=a_{n}^3-a_{n}$

I observe that:

  • $n\equiv0\pmod2 \implies a_{n}\equiv+60\pmod{1000}$
  • $n\equiv1\pmod2 \implies a_{n}\equiv-60\pmod{1000}$

How can I tackle and prove this observation?

I guess I might need to begin by converting this series from recursive to straightforward, but I'm not quite sure how to do that. Or is there a different way to approach this problem?

Thank you!


$$a_{n+1}=a_n^3-a_n=(a_n-1)(a_n)(a_n+1)$$ So if $a_k\equiv 60$ for some $k\in\mathbb{N}$ then $$a_{k+1}\equiv 59\cdot60\cdot61\equiv-60 \mod{1000}$$ $$a_{k+2}\equiv (-61)\cdot(-60)\cdot(-59)\equiv60 \mod{1000}$$ Hence as $a_0\equiv60\mod{1000}$ and $a_k\equiv a_{k+2} \text{ mod }1000$ we must have $$a_n\equiv\begin{cases}60\mod{1000}&n\equiv0\mod{2}\\-60\mod{1000}&n\equiv1\mod{2}\end{cases}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.